THE INFLUENCE OF PERCEIVED USEFULNESS, EASE OF USE, BEHAVIORAL CONTROL, SECURITY AND TRUST TOWARDS THE BEHAVIORAL INTENTION TO USE GO-PAY (A CASE STUDY ON ACCOUNTING STUDENTS IN UNIVERSITAS BRAWIJAYA) - Aziza Majid Octavika (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this study is to examines the influence of perceived usefulness, ease of use, behavioral control, security and trust to students on accounting in Universitas Brawijaya towards behavioral intention to use GoPay on GOJEK application. This study use quantitative approach. The data collection method uses survey methods. The respondents in this study are all undergraduate student of Accounting students in the Faculty of Economics and Business Universitas Brawijaya who active in the period of 2018/2019 with total 1186 students. Hypothesis testing in this study use outer model and inner model with Partial Least Square (PLS) application. The result of the examination shows that perceived usefulness, perceives behavioral control, perceived security and perceived of trust has a significant influence towards behavioral intention to use GoPay, in contrary with perceived ease of use shows that it does not have significant influence to consumers in using GoPay features on GOJEK app.Keywords: Perceived Usefulness, Ease of Use, Behavioral Control, Security, Trust, GoPay Features, GOJEK application.